Emotional Dynamics in Toxic Creative Workplaces in Southeast Asia - Nurjaya Nurjaya; Raeni Dwi Santy; Ardhi Goeliling; Fatmawati A Rahman (CV. Sakura Digital Nusantara, 2026)
Purpose – This study aims to explore the emotional dynamics of employees working in toxic work environments in the creative industries, and to understand how these conditions affect their identity, well-being, and creative processes. Design/methodology/approach – This study used a narrative inquiry approach to capture the lived experiences of participants. Data were collected through in-depth, semi-structured interviews with 18 creative professionals from the advertising, digital media, and film production sectors. Thematic narrative analysis was used to identify key patterns in their experiences. Finding/Results – The research revealed four main themes: (1) emotional dissonance and identity stress, where employees suppress authentic feelings to conform to organizational expectations; (2) burnout and emotional exhaustion resulting from chronic workloads that diminish creativity; (3) silencing and erosion of trust that undermine psychological safety and collaboration; and (4) narrative coping and resilience strategies, where employees use stories, coworker solidarity, and reframing to maintain meaning and identity. Originality/Value – This research contributes to organizational studies by situating the issues of emotional labor, burnout, and psychological safety within the context of the creative industries, where the interconnectedness of professional identity and creative output increases vulnerability to toxic environments. Methodologically, this study demonstrates the value of narrative inquiry in uncovering the complexities of work emotions and hidden resilience strategies. Practically, these findings emphasize the importance of systemic interventions and leadership practices that build trust, recognition, and psychological safety to maintain employee well-being and sustain creativity and innovation.